Extracellular pH mapping of liver cancer on a clinical 3T MRI scanner. Issue 5 (5th November 2019) - Coman, Daniel; Peters, Dana C.; Walsh, John J.; Savic, Lynn J.; Huber, Steffen; Sinusas, Albert J.; Lin, MingDe; Chapiro, Julius; Constable, R. Todd; Rothman, Douglas L.; Duncan, James S.; Hyder, Fahmeed
Abstract : Purpose: To demonstrate feasibility of developing a noninvasive extracellular pH (pHe ) mapping method on a clinical MRI scanner for molecular imaging of liver cancer. Methods: In vivo pHe mapping has been demonstrated on preclinical scanners (e.g., 9.4T, 11.7T) with Biosensor Imaging of Redundant Deviation in Shifts (BIRDS), where the pHe readout by 3D chemical shift imaging (CSI) depends on hyperfine shifts emanating from paramagnetic macrocyclic chelates like TmDOTP 5− which upon extravasation from blood resides in the extracellular space. We implemented BIRDS‐based pHe mapping on a clinical 3T Siemens scanner, where typically diamagnetic 1 H signals are detected using millisecond‐long radiofrequency (RF) pulses, and 1 H shifts span over ±10 ppm with long transverse ( T 2, 10 2 ms) and longitudinal ( T 1, 10 3 ms) relaxation times. We modified this 3D‐CSI method for ultra‐fast acquisition with microsecond‐long RF pulses, because even at 3T the paramagnetic 1 H shifts of TmDOTP 5− have millisecond‐long T 2 and T 1 and ultra‐wide chemical shifts (±200 ppm) as previously observed in ultra‐high magnetic fields. Results: We validated BIRDS‐based pH in vitro with a pH electrode. We measured pHe in a rabbit model for liver cancer using VX2 tumors, which are highly vascularized and hyperglycolytic. Compared to intratumoral pHe (6.8 ± 0.1; P < 10 −9 ) and tumor's edge pHe (6.9 ± 0.1; P < 10 −7 ), liver parenchyma pHe was significantly higher (7.2 ± 0.1). Tumor localization was confirmed with histopathological markers of necrosis (hematoxylin and eosin), glucose uptake (glucose transporter 1), and tissue acidosis (lysosome‐associated membrane protein 2). Conclusion: This work demonstrates feasibility and potential clinical translatability of high‐resolution pHe mapping to monitor tumor aggressiveness and therapeutic outcome, all to improve personalized cancer treatment planning.